Effect of the biological castration vaccine (Improvac®) on sex hormones and reproductive organs of pigs in Vietnam - Danh Cong Lai; Nam Minh Nguyen; Khanh Tran Doan Vinh; Hue Vo Thi; Phong Du Dai; Duy Tien Do (Veterinary Integrative Sciences)
The Improvac® vaccine has been shown to improve growth performance, meat quality, and sexual behavior in swine herds in several countries. This study initially investigated the ability of this vaccine to control sex hormones and the development of reproductive organs in Vietnamese crossbred pigs (Yorkshire – Landrace x Duroc). A total of 45 male piglets were randomly divided into three groups: vaccinated at 12 and 18 weeks old, surgically castrated males at 7 days old, and entire males. Meanwhile, 40 female piglets were randomly assigned to one of two groups: those vaccinated at 12 and 16 weeks of age or entire females. Serum from experimental pigs was collected monthly before and after vaccination until slaughter (25 weeks of age). At the time of slaughter, reproductive organs were obtained to assess changes at the macroscopic and microscopic features. Anti-GnRH antibodies in the immunized male and female pigs increased dramatically and remained for several weeks following a booster shot, while serum levels of sex hormones were significantly lower than in the entire group (P<0.05). In addition, the reproductive organs of the immunized groups were negatively affected compared to the control groups. The male vaccinated group showed a significant reduction in the size of reproductive organs and irreversible disruption of spermatogenesis and testicular structure. The ovary and reproductive organs in the immunized female group revealed degradation in the size and ovarian follicle development. Taken together, the Improvac® vaccine can decrease sex hormones, thereby disrupting the development of reproductive organs in vaccinated male and female pigs.